Financial destabilization - Ken-ichi Hashimoto; Ryonghun Im; Takuma Kunieda; Akihisa Shibata (Osaka University, Institute of Social and Economic Research (ISER), 2021)
This paper uses a dynamic general equilibrium model to examine whether financial innovations destabilize an economy. Applying a neoclassical production function, we demonstrate that as financial frictions are mitigated, the economy loses stability and a ip bifurcation occurs at a certain level of financial frictions under an empirically plausible elasticity of substitution between capital and labor. Furthermore, the amplitude of fluctuations increases as financial frictions are mitigated and is maximized when the financial market approaches perfection. These outcomes imply that financial innovations are likely to destabilize an economy.
Keywords: E13; E32; E44; 330; Financial innovations; endogenous business cycles; nancial destabilization; heterogeneous agents